2020
DOI: 10.1371/journal.pntd.0008794
|View full text |Cite
|
Sign up to set email alerts
|

Serious limitations of the current strategy to control Soil-Transmitted Helminths and added value of Ivermectin/Albendazole mass administration: A population-based observational study in Cameroon

Abstract: Background Soil-transmitted helminth (STH) infections remain a public health concern in sub-Saharan Africa. School-based mass drug administration (MDA) using the anthelminthic drug Mebendazole/Albendazole have succeeded in controlling morbidity associated to these diseases but failed to interrupt their transmission. In areas were filarial diseases are co-endemic, another anthelminthic drug (Ivermectin) is distributed to almost the entire population, following the community-directed treatment with ivermectin (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 24 publications
0
9
0
1
Order By: Relevance
“…The three-year retrospective survey revealed that the overall prevalence of STH was quite low (4.9%), suggestive of low endemicity levels, as was previously demonstrated during a cross-sectional prospective survey, both in the human population and the environment, conducted in the Bangangte Health District (West Region, Cameroon), located about 50 km from the Mifi Health District [17]. In fact, a continuing decreasing trend has been observed since 1987 (prior to intervention in the Mifi Division, with prevalence of 68.2% and 82.9% for A. lumbricoides and T. trichiura, respectively), suggesting a good momentum towards elimination [5,6,[10][11][12]. This could be the result of the public health interventions (Mebendazole-based deworming campaigns) that have been implemented since 2007 by the Ministry of Public Health through its National Program for Schistosomiasis and Soil-Transmitted Helminthiasis Control [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The three-year retrospective survey revealed that the overall prevalence of STH was quite low (4.9%), suggestive of low endemicity levels, as was previously demonstrated during a cross-sectional prospective survey, both in the human population and the environment, conducted in the Bangangte Health District (West Region, Cameroon), located about 50 km from the Mifi Health District [17]. In fact, a continuing decreasing trend has been observed since 1987 (prior to intervention in the Mifi Division, with prevalence of 68.2% and 82.9% for A. lumbricoides and T. trichiura, respectively), suggesting a good momentum towards elimination [5,6,[10][11][12]. This could be the result of the public health interventions (Mebendazole-based deworming campaigns) that have been implemented since 2007 by the Ministry of Public Health through its National Program for Schistosomiasis and Soil-Transmitted Helminthiasis Control [18].…”
Section: Discussionmentioning
confidence: 99%
“…The control of STH in Cameroon, as recommended by the World Health Organization (WHO) [8,9], is principally based on large-scale deworming through annual mass drug administration (MDA) of mebendazole to at-risk populations, especially pre-school and school-age children [7]. This strategy has significantly reduced the prevalence and intensity of infection, indicative of transmission interruption in certain foci [10][11][12]. However, this intervention approach, targeting only a subset of the population, even though at high risk for infestation, does not prevent re-infestation as prevalence may return to baseline levels 6-8 months after treatment [13], and the disease was found to be persisting in some foci [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…This situation probably results from the fact that (a) the health areas neighboring the TaNT villages have been treated with ivermectin for about two decades to fight onchocerciasis; (b) most of the people living in the TaNT villages benefitted from annual treatment with ivermectin between 2015 and 2018 (subjects excluded from this treatment represent less than 3% of those tested with the LoaScope); and (c) school-aged children of the whole health district have received regular mebendazole treatment since 2007. Of note, it has been shown recently that, in areas where ivermectin is administered as a mass treatment, the impact is greater on STH transmission compared to where only mebendazole has been administered [4]. Given the absence of hookworm infection, the low proportion of participants infected with T. trichiura or A. lumbricoides, and the low egg counts recorded (Table 2), STH-related blood loss in the intestine was probably minimal.…”
Section: Detection Of Soil-transmitted Helminthsmentioning
confidence: 94%
“…Anthelmintic treatment is carried out routinely as a veterinary care procedure to remove helminth infections in the Barbary macaques living at Affenberg Salem. All monkeys individually received Ivermectin (Diapec, Albrecht), a broad‐spectrum anthelmintic compound (Djune‐Yemeli et al, 2020; Heukelbach et al, 2004; Müller et al, 2017). The study animals were divided into two groups, a treatment group (eight females, five males) which received Ivermectin treatment in August 2015, and a control group (six females, four males) which did not receive the treatment at this time.…”
Section: Methodsmentioning
confidence: 99%